Molecular forces and self assembly : in colloid, nano sciences and biology - Ninham, B. W.; Lo Nostro, Pierandrea (Cambridge University Press, 2010)
Challenging the cherished notions of colloidal theory, Barry Ninham and Pierandrea Lo Nostro confront the scientific lore of molecular forces and colloidal science in an incisive and thought-provoking manner. The authors explain the development of these classical theories, discussing amongst other topics electrostatic forces in electrolytes, specific ion effects and hydrophobic interactions. Throughout the book they question assumptions, unearth flaws and present new results and ideas. From such analysis, a qualitative and predictive framework for the field emerges; the impact of this is discussed in the latter half of the book through force behaviour in self assembly. Here, numerous diverse phenomena are explained, from surfactants to biological applications, all richly illustrated with pertinent, intellectually stimulating examples. with mathematics kept to a minimum, and historic facts and anecdotes woven through the text, this is a highly engaging and readable treatment for students and researchers in science and engineering.
Keywords: Intermolecular forces.; Molecular theory.; Self-assembly (Chemistry); elektronické knihy; electronic books